Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian ASI Eksklusif Di Desa X Wilayah Kerja Puskesmas X - Grace Irene Viodyta Watung; Siska Sibua (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Exclusive breastfeeding in Indonesia needs to be increased, namely breastfeeding immediately (approximately one hour after birth) until the baby is 6 months old and providing colostrum which contains all the nutrients needed by newborns and protects the baby from disease. Busy work and reasons to maintain breast beauty are some of the reasons mothers do not give additional food to babies other than breast milk. The purpose of this study was to determine the relationship between knowledge and attitudes of mothers with exclusive breastfeeding for infants in X Village, X Health Care Centre Area. The type of research used is descriptive analytic method with a cross-sectional study approach. The population in this study were all (mothers) who had babies of 6-12 months in X Village, X Health Care Centre Area amounting to 32 people, which were determined using total sampling. Data were analyzed using the chi-square statistical test with a significance level of 95% (α): 0.05. Based on the results of statistical tests using chi-square for bivariate analysis between the relationship between knowledge and exclusive breastfeeding, the value of -value = 0.005 is smaller than the value of = 0.05. It means that H0 is rejected, then there is a relationship between mother's knowledge and exclusive breastfeeding. For bivariate analysis of the relationship between mother's attitude and exclusive breastfeeding, p value = 0.017 is smaller than = 0.05, meaning Ho is rejected, there is a relationship between mother's attitude and exclusive breastfeeding for infants in Belengan Village. The conclusions in this study are the knowledge and attitudes of mothers about exclusive breastfeeding to infants in Belengan Village are generally good; exclusive breastfeeding for infants is mostly appropriate; there is a relationship between knowledge and exclusive breastfeeding in X Village, X Health Care Centre Area; there is a relationship between mother's attitude and exclusive breastfeeding in X Village, X Health Care Centre Area. Suggestions in this study are for health workers to further improve health services, especially for posyandu cadres about exclusive breastfeeding. Promote education about exclusive breastfeeding. For institutions to add literature for the development of science and health as well as assist the implementation of the teaching and learning process; for mothers to increase their knowledge and apply exclusive breastfeeding to infants for the purpose of smooth growth and development.